Prinsip Mendengarkan dalam Pemulihan Trauma Anak di Panti Asuhan Kristen: Sebuah Pendekatan Psikoteologis - Yustinus Yustinus; Meriyana Meriyana; Romika Romika (Sekolah Tinggi Teologi Sumatera Utara, 2025)
Child trauma recovery in Christian orphanages requires a holistic approach integrating psychology and theology. However, practical models that operationally blend these two perspectives remain limited. This qualitative study aims to develop a mentoring model based on the principle of